Gamification in STEM Education: A Systematic Literature Review - Mursalin, M; Fonna, Mutia; Saputra, Eri; Ali, Muhammad; Setiawan, S (SAINTIS Publishing, 2024)
This study aims to assess the impact of gamification in STEM education by focusing on student motivation, engagement, and learning outcomes. Gamification, or the use of game elements in non-game contexts, is applied in STEM education to enhance more engaging and interactive learning experiences. The literature review is carried out in a narrative manner by analyzing relevant research in the last 10 years obtained from various databases, such as Google Scholar and IEEE Xplore. The results of the study show that gamification elements, such as leaderboards, points, and badges, are effective in increasing student motivation and engagement, especially in subjects that tend to be difficult. In addition, gamification plays an important role in the formation of collaborative skills through activities such as